EFESIENSI KELENJAR HYPOFISA IKAN MAS (Cyprinus carpio) DAN IKAN LELE DUMBO (Clarias gariepenus) TERHADAP PEMIJAHAN IKAN LELE DUMBO (Clarias gariepinus) - Nasir Ahmad (University of Prof. Dr. Hazairin, SH, 2018)
The aim of this research is to know the efficiency of hypofisa gland on spawning catfish. This research was conducted in March-July 2014, at Manggis I, RT / RW. 18/09 50, Kelurahan Dusun Besar, Gading Cempaka Subdistrict, Bengkului City. The design used was complete randomized design (RAL) with 2 treatments and 6 replications and to see the difference was done t test. The treatment consisted of P1 = Spawning dumbo catfish using hypofisa gland Goldfish, P2 = Spawning dumbo catfish using hypofisa gland Fish catfish dumbo. The use of different hypofisa glands has no significant effect on spawning time, hatchability, and the survival of dumbo catfish seeds in the hatchery of dumbo catfish. The use of one type of hypophysis gland with the most efficient recipient fish compared to the hypofisa gland is universal.